A motivational perspective on college students' intention to adopt mobile news apps - Han, Yuemin; Mahamed, Mastura; Abdullah, Zulhamri; Wan Abas, Wan Anita (2024)
Mobile News Apps (m-news) have emerged as a popular platform for accessing news content "anytime, anywhere," reflecting a growing trend in digital consumption among college students. Academics and industry professionals are increasingly interested in exploring the potential of m-news to support information dissemination. However, existing research has identified challenges in fostering m-news adoption. Prior studies have predominantly concentrated on technological factors influencing m-news usage, with limited attention to the motivations behind users' adoption, particularly among college students. This study leverages the Uses and Gratification Theory to explore the motivational drivers behind college students' adoption of Mobile News Apps. The findings indicate that students' intentions to use m-news are significantly influenced by their attitudes, which is shaped by their cognitive needs, social needs and affective needs. The article concludes by discussing the theoretical implications and practical applications of these insights.